Prevalence of Anemia and Its Determinants Among Pregnant, Lactating, and Nonpregnant Nonlactating Women in India. (August 2017) - Siddiqui, Mohammad Zahid; Goli, Srinivas; Reja, Tamal; Doshi, Riddhi; Chakravorty, Swastika; Tiwari, Chhavi; Kumar, Nomita P.; Singh, Deepshikha
Despite the existence of several policies and programs, anemia among pregnant and lactating women continues to be a serious concern for public health policy in India. The main objective of this study is to examine the prevalence and determinants of anemia among pregnant and lactating versus nonpregnant nonlactating (NP-NL) women for priority setting in health policies of the country. Data from the National Family Health Survey (NFHS3) conducted in 2005-2006 has been used for the analyses of this study. The results revealed that the prevalence of anemia was higher among lactating women (63%), followed by pregnant women (59%) than NP-NL women (53%). Younger lactating (71%) and older pregnant women (67%) had a higher burden of anemia. Along with socioeconomic factors, demographic indicators such as children ever born and program factors like nutrition advice and supplementary nutrition during anti natal care and postnatal care emerged as significant predictors in the case of anemia among both pregnant and lactating women, while socioeconomic indicators emerged as critical factors in the case of anemia among NP-NL women. Hence, targeting demographic and program factors, along with key socioeconomic and demographic factors in public health policy, is critical in reducing anemia among lactating and pregnant women, while targeting significant socioeconomic factors is the key for reducing anemia among NP-NL women.